Dinamika Pendidikan Islam di Thailand: Analisis Sejarah, Sistem Pendidikan, dan Kebijakan Negara - Bustari, Bustari; Rosyada, Dede; Zalnur, Muhammad; Sanusi, Ihsan (YASIN, 2025)
The development of Islamic education in Thailand reflects a complex dynamic shaped by historical, sociocultural, and governmental policy factors. This article aims to examine the historical background, educational system, and state policies that have influenced the existence of Islamic education, particularly in the southern provinces of Pattani, Yala, Narathiwat, and Satun—regions known as centers of the Malay-Muslim community. This community has long played a pivotal role in preserving Islamic traditions through the provision of religious education. Islamic education in Thailand has evolved along two main pathways: traditional pondok institutions that emphasize classical Islamic studies, and modern madrasahs that integrate religious curricula with general subjects in accordance with national education standards. Since the 1960s, the Thai government has implemented policies to modernize Islamic education as part of a broader strategy to improve educational quality and promote social integration. However, these policies have also raised concerns about potential cultural assimilation and the diminishing autonomy of Islamic educational institutions. Using a qualitative approach through a literature review method, the findings reveal that Islamic education in Thailand continues to undergo adaptation and renewal. Despite facing structural and political challenges, Islamic educational institutions remain essential in maintaining the religious identity and cultural heritage of the Muslim minority in a predominantly Buddhist nation.